Quantifying Energy and Water Savings in the U.S. Residential Sector - Chini, Christopher M; Schreiber, Kelsey L; Barker, Zachary A; Stillwell, Ashlynn S (Environmental science & technology, 2016)
Stress on water and energy utilities, including natural resource depletion, infrastructure deterioration, and growing populations, threatens the ability to provide reliable and sustainable service. This study presents a demand-side management decision-making tool to evaluate energy and water efficiency opportunities at the residential level, including both direct and indirect consumption. The energy-water nexus accounts for indirect resource consumption, including water-for-energy and energy-for-water. We examine the relationship between water and energy in common household appliances and fixtures, comparing baseline appliances to ENERGY STAR or WaterSense appliances, using a cost abatement analysis for the average U.S. household, yielding a potential annual per household savings of 7600 kWh and 39 600 gallons, with most upgrades having negative abatement cost. We refine the national average cost abatement curves to understand regional relationships, specifically for the urban environments of Los Angeles, Chicago, and New York. Cost abatement curves display per unit cost savings related to overall direct and indirect energy and water efficiency, allowing utilities, policy makers, and homeowners to consider the relationship between energy and water when making decisions. Our research fills an important gap of the energy-water nexus in a residential unit and provides a decision making tool for policy initiatives.